The Views of the Teacher Candidates on the Use of Kahoot as A Gaming Tool - Uzunboylu, Huseyin; Galimova, Elvira G; Kurbanov, Rashad A; Belyalova, Asiya M; Deberdeeva, Nelia А; Timofeeva, Mariia (International Journal of Emerging Technologies in Learning (iJET), 2020)
The process of integration of technology into education involves many tools and applications to be used in the classroom and outside teaching processes today. ‘Kahoot’ is one of such student response systems and is one of the primary applications that can be utilised for the purposes such as gamification, formative assessment & peer learning procedures. Such applications are widely used for the purposes of bringing a ramfication in the educarion industry now-a-days. The primary purpose of this research is to determine the opinions of teachers active in the education industry and their experience in using ‘Kahoot’ as a teaching aid in bringing the diversification in the industry. In this study, a semi-structured interview form is used as a data collection tool. Opinions of prospective teachers participating in the study is taken into consideration to form an end conclusion of this research study. The research data also involves a semi-structured student opinion form, and a procedure of content analysis is undertaken in the analysis of the data. The study group of the research consists of studying at Kazan (Volga region) Federal University, Institute of Legislation and Comparative Law under the Government of the Russian Federation, Plekhanov Russian University of Economics and Sechenov University in 38 teacher candidates. As a result of the study performed over the set of teachers and students, it was concluded that the ‘Kahoot’ program is widely beneficial for students and teachers. It was also concluded that the Kahoot program is helpful in eliminating the deficiencies in learning. However one of the shortcomings of the ‘Kahoot’ program is that it is an internet-based programme. Hence it may be problematic for some of the students to to use the programme who have a fewer knowledge in the internet domain. At the end of the study, a positive set of opinions about the Kahoot program is suggested, which majourly revolves around the idea that the programme is not internet based.